2010
DOI: 10.1111/j.1651-2227.2010.01860.x
|View full text |Cite
|
Sign up to set email alerts
|

Guillain‐Barré syndrome in a child with pain: lessons learned from a late diagnosis

Abstract: Pain and gait difficulties can be the main features of paediatric GBS at presentation. In addition, a comprehensive neurological exam in any case of weakness or diffuse pain combined with ongoing critical interpretation of a disease course allows for adjustment of a preliminary diagnosis towards a potentially life-threatening disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…As limitation of the present study lies in its retrospective nature, the conclusion reached requires further confirmation in a prospective study based on a larger number of cases. It has been reported that, in GBS patients with severe pain, the contrast enhancement on magnetic resonance imaging is seen in the nerve roots . Among the present 10 cases with pain, Lasègue's sign was positive in two cases; and one of the patients (case 7), in whom the magnetic resonance imaging was evaluated, showed contrast enhancement in the lumbar nerve roots.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…As limitation of the present study lies in its retrospective nature, the conclusion reached requires further confirmation in a prospective study based on a larger number of cases. It has been reported that, in GBS patients with severe pain, the contrast enhancement on magnetic resonance imaging is seen in the nerve roots . Among the present 10 cases with pain, Lasègue's sign was positive in two cases; and one of the patients (case 7), in whom the magnetic resonance imaging was evaluated, showed contrast enhancement in the lumbar nerve roots.…”
Section: Discussionmentioning
confidence: 49%
“…It has been reported that, in GBS patients with severe pain, the contrast enhancement on magnetic resonance imaging is seen in the nerve roots. 6,15,19 Among the present 10 cases with pain, Las egue's sign was positive in two cases; and one of the patients (case 7), in whom the magnetic resonance imaging was evaluated, showed contrast enhancement in the lumbar nerve roots. In the remaining cases, however, spinal magnetic resonance imaging was not obtained.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…There may be several reasons for these discrepancies. GBS is more difficult to diagnose in younger age groups, especially in pediatric patients, and varying rates in some study areas may reflect diagnostic uncertainty and either over-or underdiagnosis of GBS in younger patients [35,36] . The lower incidence of GBS in older age groups may reflect a survivor bias, in which individuals surviving into their 80s and 90s are less likely to develop GBS, although there is no substantiated biological basis for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%